The Main Prevention of Pressure Sores in Stroke - Alimansur, M; Santoso, P (International Journal of Psychosocial Rehabilitation, 2020)
Stroke is a neurological disorder that most often causes paralysis. Paralysis and weakness causes stroke patients to have bedrest for a long time. Long bedrests cause stroke patients at high risk for developing pressure sores. Prevention of pressure sores is very important by minimizing the risk factors for pressure sores. The purpose of this study is to determine the main precautions that cover wound care, fulfilment of nutrition and appropriate mobilization to prevent the occurrence of pressure sores. The research design used was descriptive analytic with the study respondents being stroke patients hospitalized in Gambiran Hospital, Kediri City. Sampling uses purposive sampling with a sample size of 40 respondents. The results of the analysis Ordinal Regression show nutritional fulfilment, mobilization and skin care have a p-value greater than 0.05, which means that the three actions can prevent the occurrence of pressure sores. Skin care, nutritional fulfillment and mobilization will maintain skin moisture, facilitate blood flow, and ensure adequate delivery of oxygen and protein to the skin. Prevention of pressure sores should be done early so that pressure sores do not occur.